Trinity and man : Gregory of Nyssa's Ad Ablabium - Maspero, Giulio. (Vigiliae Christianae, Supplements, 2007)
Why is it that when we speak of three human subjects, we speak of a unique nature, but we say that they are "three men", while when we speak of the Trinity, we speak again of a unique nature, but we say that they are "one God"? Gregory of Nyssa gives the answer in his Ad Ablabium , work that lately is the focus of a discussion about the interpretation of Gregory's thought and the social analogy of the Trinity. Trinity and Man is the first monograph devoted entirely to this tract and contributes to the debate, offering a commentary to the text, which follows the development of the Nyssian arguments and frames them in the context of Gregory's theological grammar.